Determinants of Union Commitment Among University Faculty - Ng, Ignace (Relations industrielles / Industrial Relations, 1989)
This paper investigates the relationship between the union commitment of faculty members and a number of factors, including job satisfaction, general union beliefs, attitude towards the university, work aspects and demographic characteristics. The results show that faculty members are committed to both the university and the Association. Dissatisfaction with the university administration fosters union commitment whereas negative attitudes towards unions in general reduce that commitment. Demographic characteristics and work aspects have little influence on the faculty commitment to the Faculty Association.